Total factor productivity analysis of Malaysia Airlines: Lessons from the past and directions for the future - See K.F.; Abdul Rashid A. (JAI Press, 2023)
The main objective of the study is to measure the total factor productivity (TFP) growth of Malaysia Airlines (MAS) over a 34-year period from 1980 to 2013 using a Trnqvist index method. Labour, capital, fuel and other inputs are selected as input measures, whereas the number of passengers, cargo and mail carried and non-traffic revenue are chosen as output measures in the measurement of MAS's productivity. The study revealed that MAS obtained a slow growth in TFP over the study period. The results showed that the privatisation of MAS was not sufficient to produce improved TFP performance. Furthermore, the study also found that the average stage length and load factor are interrelated with the TFP levels in a positive direction. Overall, this study extends the discussion of efficiency and productivity in the airline industry in Malaysia. 2016 Elsevier Ltd